Molecular phylogeny, including a new species of Anindobothrium (Cestoda, Rhinebothriidea) from the Southern eagle ray Myliobatis goodei, finally solves the taxonomic enigma of Phyllobothrium myliobatidis - Garcia Facal, Guillermina (2024)
During a parasitological survey of tapeworms from Myliobatis goodei Garman, 1885 (Myliobatiformes: Myliobatidae) in coastal waters off Argentina in the Southwestern Atlantic, a new rhinebothriidean cestode species, Anindobothrium danielae sp. nov., is described using morphological and molecular techniques. This species differs from its congeners by a particular combination of features, including the configuration of the bothridia, the number of marginal loculi, and the number and distribution of testes. Additionally, Anindobothrium myliobatidis comb. nov. is proposed based on several morphological traits, including the presence of stalked bothridia with marginal loculi and an apical sucker, euapolytic strobila, and postvaginal testes. The diagnosis of the genus Anindobothrium Marques, Brooks & Lasso, 2001 is amended to include the features exhibited by these two species; two species subsets are suggested based on the configuration of the bothridia. The presence of A. danielae sp. nov. and A. myliobatidis comb. nov. in the studied area not only increases the number of cestodes in M. goodei here from eight to ten but also represents the first report of a rhinebothriidean cestode parasitizing stingrays of the family Myliobatidae in the Southwestern Atlantic.